Case report: A novel loss-of-function pathogenic variant in the KCNA1 cytoplasmic N-terminus causing carbamazepine-responsive type 1 episodic ataxia - Manville, Rían W.; Sidlow, Richard; Abbott, Geoffrey W. (Frontiers in Neurology, 2022)
Episodic ataxia is an umbrella term for a group of nervous system disorders that adversely and episodically affect movement. Episodes are recurrent, characterized by loss of balance and coordination and can be accompanied by other symptoms ranging from nausea to hemiplegia. Episodic Ataxia Type 1 (EA1) is an inherited, autosomal dominant disease caused by mutations in KCNA1, which encodes the voltage-gated potassium channel, KCNA1 (Kv1.1). Here we report a novel loss-of-function KCNA1 mutation [c.464T>C/p.L155P] causing frequent, sudden onset of clumsiness or staggering gait in the young female proband. The mutation was maternally inherited and the mother, whose symptoms also began in childhood, has a normal MRI and EEG, slurred speech and dystonic movements involving upper extremities and mouth. Both mother and daughter are responsive to carbamazepine. Cellular electrophysiology studies of KCNA1-L155P potassium channels revealed complete but non-dominant loss of function, with reduced current and altered gating in heterozygous channels. To our knowledge this is the first EA1-associated mutation located in the KCNA1 cytoplasmic N-terminus.